APLIKASI E-VOTING UNTUK MENGUKUR TINGKAT KEPUASAN MASYARAKAT TERHADAP ARAH KEBIJAKAN PEMERINTAH KOTA BAUBAU DALAM PERENCANAAN PEMBANGUNAN DAERAH - Ery Muchyar Hasiri; Asniati Asniati; Nur Israwati (Prodi Teknik Informatika Unidayan Baubau, 2022)
Community satisfaction is the opinion of the community in obtaining services from public administration apparatus by comparing expectations and needs. To find out whether the development plan and direction of government decisions are running as they should, it is necessary to evaluate the performance of an agency. The purpose of this research is to build an application that can inform development planning and determine the results of community satisfaction through the e-voting system and to implement the online questionnaire feature into the e-voting system intended for the community. This application is created using web programming (HTML, PHP, Javascript) then converted into an Android application using the Apk Builder. Determination of voting on development planning uses questionnaire data, where the results of filling out the questionnaire are processed using a Likert scale. Likert scale 1-5 choices, with gradations from Strongly Agree (SS) to Strongly Agree (SS) A with a weight value of 88.31 - 100.00, Agree (S) with a weight value of 76.61 - 88.30, Doubt - Doubtful (RG) with a weight value of 65.00 - 76.60, Disagree (TS) with a weight value of 15.00 - 64.99. The results of this research are in the form of an e-voting information system application for community satisfaction with development plans and the direction of government decisions which can make it easier for the community to find out about development plans that have been decided by the local government and there are e-voting facilities to regulate the level of community satisfaction with government development plans. Baubau City.